Diagnosis value of prostate specific antigen density (PSAD) and prostate specific antigen (PSA) in bone metastases of prostate cancer among Indonesian population - Ahmad Zulfan Hendri; Andy Zulfiqqar; Indrawarman soeharjo; Raden Danarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Cancer prostate (PCa) is currently reported as the most diagnosed cancer in males. Bone metastases in PCa indicate poor prognosis and the major cause of pain and death. Early diagnosis of metastases is important in PCa management. Prostate specific antigen (PSA) velocity was used to predict overall survival and metastasis-free survival. However, this test should be conducted 2 times, for at least 4 weeks apart. Therefore, a cross-sectional test with higher positive probability value is needed. This study aimed to compare PSA density (PSAD) and PSA level to evaluate patients at risk of bone metastases in Yogyakarta, Indonesia. Aretrospective study with a total subject of 106 patients with (n = 31) and without (n = 75) bone metastases were analyzed. The initial PSA measurement, as well as bone scan and prostate volume, were evaluated in all patients. Bone survey found to be positive in 31/106 (29.2%) patients. The total of 50(47.2%), 10(9.4%) and 46(43.4%) patients had PSA level <50, 50-100 and >100ng/mL, respectively. Furthermore, receiver operating characteristic (ROC) area under the curve of PSAD (0.75) was higher that that ofPSA (0.65).PSAD more than 0.15 indicated sensitivity of 93% and specificity of 38%, while PSA more than 20 ng/mL shown sensitivity 82% and specificity 21%. In conclusion, PSAD level more than 0.15 shows high sensitivity and specificity in causing potential skeletal metastases. Using this PSAD cut-off value, unnecessary investigation canbe avoided.